Sucrose alleviates capsaicin-induced tongue burning: An in vivo study - Duangchewan Puengsurin (2022)
Background: Spicy foods are flavorful and stimulate salivation, which is beneficial for individuals with poor appetite They are also ubiquitous in many regional cuisines, but the chemical compounds in such foods, especially capsaicin from chili peppers, can cause tissue inflammation and generate intolerable burning pain in the oral cavity. Material and Methods: To identify a potential method to reduce capsaicin-induced burning pain without influencing food flavor, we tested the effects of mouth rinsing with various concentrations of sucrose. Inclusion criteria were good general and oral health, while exclusion criteria were poor baseline smell or taste, capsaicin allergy, and current orofacial pain complaints. To define an appropriate capsaicin dose, participants placed filter paper strips impregnated with 0.003%–0.3% capsaicin on the tip of the tongue and rated burning sensation by visual analog scale (VAS) score. Results: A 0.1% capsaicin solution induced tongue burning in the midrange (VAS = 6.33 ± 0.52) and so was used for subsequent tests. We then examined the efficacy concentration of sucrose for reducing tongue burning by recording VAS scores at multiple time points following a 15-s oral rinse with various aqueous sucrose solutions (5%, 10%, and 20%), milk, or pure water (control) after 0.1% capsaicin application. Scores were compared at each time point by one-way ANOVA with post hoc Dunnett’s tests. A 15-s rinse with 20% sucrose significantly alleviated burning pain compared to water rinse at 45, 60, 120, and 180 s after capsaicin exposure. Conclusions: Thus, periodic rinsing with 20% aqueous sucrose may help promote spicy food consumption among individuals with poor appetite.